Best Practice of Summative Assessment for Arabic Writing Proficiency: Evidence from Pondok Pesantren Modern Ar-Rahmah Kediri, Indonesia - Muslimah, Maziyyatul; Sulalah, Iin Anis; Rohmawati, Rosalina; Sofi, Niswatus; Zunairoh, Yuyun (Asalibuna, 2024)
Writing proficiency (maharah kitabah) is a fundamental yet demanding component of Arabic language education. In pesantren contexts, where tradition and discipline are central, effective assessment strategies remain underexplored. This study investigates the best practices in implementing summative assessment for Arabic writing at Pondok Pesantren Modern Ar-Rahmah Kediri. Using a qualitative case study approach, data were gathered through classroom observation, interviews, and document analysis. The study identified three significant best practices: (1) the contextual use of imla’ al-istima’i (auditory dictation) as a summative tool that simultaneously assesses listening and writing skills; (2) the integration of formative and summative assessments to scaffold students' learning progress systematically; and (3) the application of standardized, transparent rubrics to ensure fairness and clarity in evaluation. These practices collectively foster writing accuracy, vocabulary enrichment, grammatical mastery, and learner autonomy. Despite these strengths, a notable percentage of students remain below the expected proficiency level, indicating a need for enhanced remedial support. Future research should explore how digital tools and AI-driven feedback systems can further optimize these best practices and promote scalable, individualized Arabic writing assessments.